Research on radiocarbon calibration records, focussing on new measurements from Lake Suigetsu, Japan - Staff, RA (2011)
Radiocarbon calibration is a fundamental stage of the radiocarbon dating process if meaningful calendar ages are to be derived from samples’ radiocarbon determinations. However, the present limit of direct, non-reservoir-corrected, atmospheric radiocarbon calibration is 12,550 calibrated years before present (Reimer et al. 2009), leaving approximately three quarters of the radiocarbon timescale to be necessarily calibrated via less secure marine records. The sediment profile of Lake Suigetsu, Honshu Island, central Japan, offers an ideal opportunity from which to derive an extended, ‘wholly terrestrial’ and continuous record of atmospheric radiocarbon back to the limits of radiocarbon detection (circa 60,000 years before present). The presence of well-defined, annually-deposited laminae (varves) throughout this extended time period provides an independent, high resolution chronometer against which radiocarbon measurements, performed upon plant macrofossil samples retrieved from the sediment column, can be directly related. This site was first exploited for radiocarbon calibration purposes by Kitagawa and van der Plicht (1998a, 1998b), however, issues pertaining to the reliability of the calendar age scale of this work precluded the widespread uptake of this dataset. The work presented in this DPhil thesis represents a significant contribution to the broader, ‘Suigetsu Varves 2006’ project – an international collaboration centring on the re-coring of Lake Suigetsu, which was undertaken in summer 2006 to improve upon the shortcomings of the previous project and, thereby, to fully exploit the site’s potential for both radiocarbon calibration and multi-proxy palaeoenvironmental study (Nakagawa et al. 2011). This DPhil thesis describes the generation of the revised (‘SG06’) terrestrial radiocarbon calibration dataset from Lake Suigetsu, comprising 647 accelerator mass spectrometry (AMS) radiocarbon determinations, and extending across the complete range of the radiocarbon dating method. Furthermore, visual matching of archive SG93 core sections to the continuous SG06 sediment profile was undertaken, allowing the integration of the ≈ 300 radiocarbon determinations from the original Lake Suigetsu project into a higher resolution (≈ 900 radiocarbon measurements), combined Lake Suigetsu radiocarbon calibration dataset, providing a unique reconstruction of atmospheric radiocarbon across the entire radiocarbon dating timescale. Kitagawa H and van der Plicht J (1998a) Science 279, 1187-1190. Kitagawa H and van der Plicht J (1998b) Radiocarbon 40 (1), 505-515. Nakagawa T et al. (2011) Quaternary Science Reviews, in press. Reimer PJ et al. (2009) Radiocarbon 51 (4), 1111-1150.